Procedure for Giving Compensation to Victims of Environmenental Pollution in the Sidoarjo bio Industrial Area - Shadam Teja Kusuma; Budiarsih Budiarsih (Activa Yuris: Jurnal Hukum, 2023)
Pollution not only affects people's lives today, but also threatens their survival in the future. If one of the parties who are harmed or harmed feels harmed by an activity that pollutes or damages the environment so that the occurrence of this can turn into an environmental conflict. Requirements for compensation for parties harmed by environmental factors were previously regulated in the elucidation of the Regulation of the State Minister for the Environment Number 13 of 2011, but implementation was not carried out. So that every citizen or community has the right to a healthy and good environment that is bound to protect the environment and also to prevent and mitigate environmental pollution and damage, protect and manage the environment as a form of human endeavor in carrying out its interactions with the environment in order to sustain life to achieve prosperity and environmental sustainability. The criteria for compensation for victims of pollution are regulated by changes in the value of property before and after pollution and/or environmental damage, how to value community assets, how to calculate additional costs and cost prevention, loss of income, changes in operations, and money generated by pollution and/or environmental damage, as well as medical costs. If the polluter is required to include costs of pollution and/or environmental damage into the calculation of production costs, operational and/or operational costs, in addition to paying the agreed compensation, then the compensation is considered reasonable. An obstacle to paying proper compensation to victims of pollution is the lack of human resources in the area, such as experts in calculating environmental compensation. Compensation must be carried out according to the procedures of the Environmental Agency and special laws, so that the person concerned bears legal responsibility for losses paid to victims of environmental damage. For this reason, the formulation of the problem can be found, namely what is the procedure for providing compensation for environmental pollution in the bio-industrial area